Aging and choice - Betty E. Tanius; Stacey Wood; Yaniv Hanoch; Thomas Rice (Judgment and Decision Making, 2009)
We examined choice behavior in younger versus older adults using a medical decision-making task similar to Medicare Part D. The study was designed to assess age differences in choice processes in general and specifically designed to examine the effect of choice set size on performance. Data are drawn from a larger study on choice and aging, in which ninety-six younger adults (ages 18--64) and 96 older adults (ages 65--91) selected a prescription drug plan from either 6 or 24 different options. As hypothesized, choice set size was a significant predictor of individuals' ability to choose the best plan. Participants who were presented with 24 plans were less likely to choose the correct prescription drug plan. Age did not have a negative effect on decision performance; however numeracy and speed of processing significantly affected performance across groups. Older adults were more likely to be characterized as satisficers on a decision personality measure, but this categorization did not predict performance on the choice task.